Opieka nad sierotami we wczesnonowożytnym Kleczewie - Hajdrych, Łukasz (Biuletyn Historii Wychowania, 2020)
The care of orphans was one of the main concerns of early modern magistrates across the whole Europe. In each country and town this care could take a completely different form, ranging from placing parentless children in asylums to assigning them to certain families. This paper deals with the problem of the orphan-care in a small town of the Great Poland region in 17th and 18th centuries, on the example of private town of Kleczew, located in the east part of the region.